Health service utilisation and unmet healthcare needs of Australian children from immigrant families: A population‐based cohort study. (23rd June 2020) - Guo, Shuaijun; Liu, Mengjiao; Chong, Shiau Yun; Zendarski, Nardia; Molloy, Carly; Quach, Jon; Perlen, Susan; Nguyen, Minh Thien; O'Connor, Elodie; Riggs, Elisha; O'Connor, Meredith
Abstract: Compared with most other Organization for Economic Co‐operation and Development (OECD) countries, information about the patterns of health service use for children from immigrant families in Australia is currently limited, and internationally, data on unmet healthcare needs are scarce. This study aims to examine the distribution of health service utilisation and unmet healthcare needs for immigrant children aged 10–11 years in Australia. We drew on data from the Longitudinal Study of Australian Children Birth (B; n  = 5, 107) and Kindergarten (K; n  = 4, 983) cohorts. The exposure was family immigration background collected at 0–1 (B‐cohort) and 4–5 (K‐cohort) years. Outcomes were parent‐reported child health service use and unmet healthcare needs (defined as the difference between services needed and services received) at 10–11 years. Logistic regression analyses were used to examine associations between family immigration background and health service use/unmet healthcare needs, adjusting for potential confounders. Results showed that one‐third of Australian children (B‐cohort: 29.0%; K‐cohort: 33.4%) came from immigrant families. There were similar patterns of health service use and unmet healthcare needs between children from English‐speaking immigrant and Australian‐born families. However, children from non‐English‐speaking immigrant families used fewer health services, including paediatric, dental, mental health and emergency ward services. There was a disparity between the services used when considering children's health needs, particularly for paediatric specialist services (B‐cohort: OR = 2.43, 95% CI 1.11–5.31; K‐cohort: OR = 2.72, 95% CI 1.32–5.58). Findings indicate that Australian children from non‐English‐speaking immigrant families experience more unmet healthcare needs and face more barriers in accessing health services. Further effort is needed to ensure that the healthcare system meets the needs of all families.